Risk factors for spontaneous preterm delivery. Issue 1 (10th June 2020) - Cobo, Teresa; Kacerovsky, Marian; Jacobsson, Bo
Abstract: Background: There is a substantial variation in rates of preterm delivery between different parts of the world. The understanding of these variations, as well as the biological mechanisms behind spontaneous preterm delivery, is limited. Although the benefit of antenatal interventions has been shown to be limited, using well‐known risk factors for spontaneous preterm delivery to select the correct pregnant women for targeted interventions is important from both a medical and caregiving perspective. Objective: To provide an introduction to a substantial research area dealing with risk factors of spontaneous preterm delivery. Methods: Risk factors in this review were classified as demographical, obstetrical, and gynecological and those related to the current pregnancy according to high‐quality evidence of recent literature. Results and Conclusion: An introduction to a substantial research area in maternal and fetal medicine was provided that might help clinicians to better understand the risk factors related to preterm delivery and select the correct pregnant women for targeted interventions. Abstract : This review article will provide an introduction to a substantial research area: risk factors for spontaneous preterm delivery.